STANDAR PENILAIAN KEKHASAN SEKOLAH ISLAM TERPADU - Merri Yelliza; Wirma Datil Husna; Nurtika Syafitri; Dewi Oktavia; Titit putriani; Masidah Daulay (EDU RESEARCH, 2024)
Assessment is an activity or process that involves collecting and processing information to measure and analyze the achievement of student learning outcomes. This research method adopts a qualitative approach by applying literature study techniques. Using literature studies, this research focuses on collecting, analyzing, and interpreting information available in the form of writings, articles, books, or journals that can provide insights related to the phenomenon being researched. This literature study shows that the assessment standards in Integrated Islamic schools aim to shape the character of students based on religious, nationalist, independent, mutual cooperation, and integrity values. The assessment is carried out comprehensively by involving an evaluation of students' attitudes, knowledge, skills, and morals. This assessment process prioritizes a structured and based approach on character development in accordance with Islamic teachings and universal social norms. Moral assessment has an important role in strengthening students' moral values, helping them adjust to the social environment, and supporting the formation of a good personality in the context of Islamic education. Keywords: Assessment, Studi Literatur, Islamic School.